PEMANFAATAN MEDIA SOSIAL SEBAGAI SARANA MEDIA DAKWAH BAGI MAHASISWA MANAJEMEN DAKWAH FAKULTAS USHULUDDIN ADAB DAN DAKWAH IAIN KERINCI ANGKATAN 2021: TUTI MAHARANI - Maharani, Tuti (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2024)
In the era of increasingly advanced digitalization, social media has played an important role in various aspects of life, including as a medium for preaching. Social media allows individuals and religious communities to share messages of goodness and religious values ​​quickly and widely with a wider audience through platforms that are accessible to many people. The aim of this research is to determine the use of social media as a means of da'wah media for da'wah management students class of 2021. This research uses a qualitative approach. The research results of the use of social media by missionary management students have proven to be effective in spreading religious messages to a wider audience. Social media's ability to reach diverse audiences and to convey messages quickly and interactively makes it a powerful tool for da'wah. This is proven by the fact that many da'wah management students are interested in watching videos uploaded by da'wah that are distributed on social media. Not just watching, da'wah management students also participated in the form of questions in the comments column of social media accounts that uploaded da'wah videos. Da'wah management students also shared preaching videos that they thought were interesting to share in WhatsApp groups.